Optimized stacked long short-term memory with hyperbolic secant activation function for Alzheimer’s disease classification - Maaram, Krishna Kishore; Chandre, Shanker (Biomedical signal processing and control, 2025)
Alzheimer’s Disease (AD) is a progressive disorder that results in reflective failure in human memory and cognition. The existing methods have a high learning rate which affects the model stability and generates poor generalizability thereby reducing classifier accuracy. Therefore, the Stacked Long Short-Term Memory (SLSTM) with hyperbolic secant (Sech) activation function is proposed in this research for classifying AD diseases. To enhance the classifier performance, the hyperparameter tuning is applied by using the Crisscross Strategy based Parrot Optimization Algorithm (CSPOA). The sech function has a moderate slope which potentially leads to reduced vanishing gradient issues. The hidden layer of SLSTM creates a model for deeper and more accurate learning of description. The model parameters are spread in the entire space without enhancing memory capacity thereby enabling convergence and nonlinear operations of data. The flipping is applied for AD, Cognitively Normal (CN) and Mild Cognitive Impairment (MCI) classes of Magnetic Resonance Imaging (MRI) and Positron Emission Tomography (PET) data to augment the images and min–max normalization is applied for augmented AD, CN and MCI classes. The optimized SLSTM with Sech based classifier attained 99.18% accuracy for the class of AD vs CN, 99.52% accuracy for MCI vs CN, 99.17% accuracy on MCI vs AD and 98.25% accuracy for AD vs CN vs MCI which is better than Multimodal image feature fusion.